Chronic Deep Brain Stimulation of the Hypothalamic Nucleus in Wistar Rats Alters Circulatory Levels of Corticosterone and Proinflammatory Cytokines - Juan Manuel Calleja-Castillo; Dora Luz De La Cruz-Aguilera; Joaquín Manjarrez; Marco Antonio Velasco-Velázquez; Gabriel Morales-Espinoza; Julia Moreno-Aguilar; Maria Eugenia Hernández; Lucinda Aguirre-Cruz; Lenin Pavón (Clinical and Developmental Immunology)
Deep brain stimulation (DBS) is a therapeutic option for several diseases, but its effects on HPA axis activity and systemic inflammation are unknown. This study aimed to detect circulatory variations of corticosterone and cytokines levels in Wistar rats, after 21 days of DBS-at the ventrolateral part of the ventromedial hypothalamic nucleus (VMHvl), unilateral cervical vagotomy (UCVgX), or UCVgX plus DBS. We included the respective control (C) and sham (S) groups (n=6 rats per group). DBS treated rats had higher levels of TNF-α (120%; P<0.01) and IFN-γ (305%; P<0.001) but lower corticosterone concentration (48%; P<0.001) than C and S. UCVgX animals showed increased corticosterone levels (154%; P<0.001) versus C and S. UCVgX plus DBS increased IL-1β (402%; P<0.001), IL-6 (160%; P<0.001), and corsticosterone (178%; P<0.001 versus 48%; P<0.001) compared with the C and S groups. Chronic DBS at VMHvl induced a systemic inflammatory response accompanied by a decrease of HPA axis function. UCVgX rats experienced HPA axis hyperactivity as result of vagus nerve injury; however, DBS was unable to block the HPA axis hyperactivity induced by unilateral cervical vagotomy. Further studies are necessary to explore these findings and their clinical implication.